Aspectes formals de les preposicions en català - Sancho Cremades, Pelegrí (Caplletra. Revista Internacional de Filologia, 1995)
Studies on the prepositional category generally cover its syntactic and semantic aspects. Phonological aspects are usually reflected in a peripheral way. In this article we propose to study some of the phonic features of Catalan prepositions from the point of view of Cognitive Grammar, and try to establish to what extent these are exclusively phonological facts. Specifically, we shall study the atonicity of the most prototypical prepositions, the exceptional accentuation of prepositions, the so-called contractions of prepositions and articles, and the a/e and a/ad alternations in Northern Catalan and colloquial Valencian, respectively.